The dark side of batteries: Child labor and cobalt mining in the Democratic Republic of Congo - Maurizio Malpede (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2022)
This paper provides evidence that the rapid increase in the demand for lithium-ion batteries has reduced the education rates of individuals living in cobalt-rich regions of the Democratic Republic of the Congo (DRC). In contrast with other minerals, I find that children in cobalt-mining villages are more likely to work outside their domestic environment and less likely to be in school. I also show that children exposed to cobalt mining are associated with lower cognitive and physical development. These results were obtained by exploiting the exogenous geographic variation of cobalt deposits before the sharp increase in the worldwide demand for cobalt-based electric batteries and using individual education attainment data. These findings suggest that the lower educational achievement of children living in cobalt-rich communities of the DRC is caused not only by a lack of solid child labor regulations (CLRs) but also by a mining industry that generates pollution.
Keywords: I25; J13; O13; 330; Lithium-ion Batteries; Cobalt Mining; Child Labour